Analisis Saluran Pemasaran Opak Singkong (Studi Kasus Di Desa M Sitiharjo Kabupaten Musi Rawas) - Ira Primalasari; Vera Octalia (Program Studi Agribisnis Universitas Sumatera Selatan, 2023)
The purpose of this research to analyse of marketing channel of opak cassava and analyse the costs and the amount of margin received by cassava opak craftsmen in M Sitiharjo Village.This research method uses a survey method with a case approach to opak craftsmen in M Sitiharjo Village, Musi Rawas Regency. The data used in the study used primary data and secondary data. The sampling technique of marketing institutions in this study using Snow Ball Sampling technique. The results showed that the marketing channel that occurs in opak products in M Sitiharjo Village has 4 marketing channels. The longest channel is from marketing channel 1, while the shortest channel is marketing channel 4. The highest marketing margin lies in marketing channels 2 and 3. While the highest producer's share lies in marketing channel 4. This is due to the absence of marketing institutions involved.